2019
DOI: 10.1021/acs.langmuir.9b02128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Alkyl Chain Length of Amphiphilic Ionic Liquids on the Structure and Dynamics of Model Lipid Membranes

Abstract: We compare the biophysical and structural aspects of the interaction of amphiphilic ionic liquids containing 1-alkyl-3-methylimidazolium cation ([C n MIM] + , n = 8, 12, or 16) with membranes composed of zwitterionic 1-palmitoyl-2-oleoyl-snglycero-3-phosphocholine (POPC) or anionic 1-palmitoyl-2-oleoyl-sn-glycero-3phospho-rac-glycerol (POPG). Liposome affinity and permeabilization were determined using ζ-potential and fluorescence studies, correlated with the cytoxicity of [C n MIM] + Br − toward HeLa cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(100 citation statements)
references
References 50 publications
(92 reference statements)
7
93
0
Order By: Relevance
“…14 Cytotoxicity of ionic liquids is rooted in the amphiphilic nature of cations, and is known to correlate directly with length of alkyl chains. 15 Various computational studies, [16][17][18] and investigations based on neutron reflectometry [19][20] and solid-state NMR 15,21 have revealed the structural details of their interaction with lipid bilayers. In this mechanism, the alkyl chain enters the hydrophobic phase (OL of bilayer) while the charged head group resides at the lipid-water interface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Cytotoxicity of ionic liquids is rooted in the amphiphilic nature of cations, and is known to correlate directly with length of alkyl chains. 15 Various computational studies, [16][17][18] and investigations based on neutron reflectometry [19][20] and solid-state NMR 15,21 have revealed the structural details of their interaction with lipid bilayers. In this mechanism, the alkyl chain enters the hydrophobic phase (OL of bilayer) while the charged head group resides at the lipid-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…In this mechanism, the alkyl chain enters the hydrophobic phase (OL of bilayer) while the charged head group resides at the lipid-water interface. 15,[19][20][21] Insertion of cations in this manner puts the OL under strain ultimately leading to membrane permeabilization and disruption. 22 A similar mechanism could also lead to fusion of vesicles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison between POPC and POPG tells us that LUVs of former require lower [C 12 MIM] + Brconcentrations to fuse. This is counter-intuitive from an electrostatic point of view since [C 12 MIM] + bound POPC LUVs possess a net positive surface charge and hence should be less However, insertion of [C 12 MIM] + molecules renders POPC bilayers more disordered (<S>=0.127) as compared to POPG (<S>=0.154),15 a factor which could assist membrane fusion through surface exposure of hydrophobic tails thus overcoming the hydration barrier 40. Some membrane fusion models have suggested that formation of an initial contact between merging bilayers known as prestalkmembrane 37,[41][42].…”
mentioning
confidence: 99%
“…Even at 1 mM, where no [C 12 MIM] + Brinduced fusion is expected, one observes 6% and 2% total lipid mixing in POPC and POPG LUVs, respectively. The observed difference is probably due to the fact that more [C 12 MIM] + molecules bind POPC (K= 590 ± 60 mM -1 ) as compared to POPG (K= 340 ± 30 mM -1 ) membranes 15. In a probe dilution assay, this value will depend on the lateral diffusion of lipids in a bilayer which once again highlights themore dynamic nature of POPC bilayers in presence of [C 12 MIM] + .…”
mentioning
confidence: 99%